Governance of Investment in Tangerang Region Review of State Administrative Law: Tata Kelola Investasi Daerah Tangerang Tinjauan Hukum Administrasi Negara - Annisa, Reza; Putra Nugraha, Dwi; Widya Nirwana, Clara; Titania Aurelia Mulia, Clarissa; Atara, Irvin (Fakultas Hukum Universitas Jambi, 2025)
This study examines investment governance in Tangerang City from the perspective of Administrative Law, focusing on the implementation of local government authority in attracting and managing investment based on the principles of good governance. Although Tangerang City demonstrates dynamic economic growth, there remains a significant disparity between well-developed areas such as BSD City and Alam Sutera and other regions that have not benefited equally from development. This situation raises administrative-legal issues regarding the effectiveness of local government authority in fulfilling the principles of equity and justice as mandated by Law No. 23 of 2014 on Regional Government and Law No. 30 of 2014 on Administrative Governance. The main problem addressed in this study concerns how the Tangerang City Government exercises its administrative and legal responsibilities in managing investment potential to ensure not only economic growth but also equitable distribution of economic benefits across regions. This research fills a gap in existing studies on Administrative Law, which have predominantly focused on investment licensing and bureaucracy, by emphasizing the dimension of equitable benefit distribution and the implementation of administrative authority at the regional level. The objective of this study is to analyze the position, implementation, and challenges of administrative authority in creating transparent, accountable, and equitable investment governance consistent with the General Principles of Good Governance. Using a normative juridical method, supported by an empirical approach, this research examines relevant laws and regulations governing regional administration, administrative governance, and investment management while analyzing the factual conditions in Tangerang City. The findings reveal that although the city government has adopted the Regional Investment Plan as a legal instrument of administrative authority, its implementation has yet to achieve equitable outcomes across all areas. Therefore, strengthening the administrative legal framework in investment planning, facilitation, and supervision is essential to establish inclusive, efficient, and socially just investment governance consistent with constitutional mandates.